Gradual introduction of multiple active sites in quest of high activity metal-free oxygen reduction catalysts and exploring the synergistic effect - Guo, Qi; Ma, Shuai; Wu, Qi-Long; Liu, Zhi-Zhuang; Yao, Zhao-Quan; Li, Shuai; Zhao, Jiong-Peng; Liu, Fu-Chen (Inorganic chemistry frontiers, 2023)
The use of metal-free carbon nanomaterials as cathodic oxygen reduction reaction (ORR) catalysts has rapidly grown due to their low cost, high electrical conductivity, and great stability. Recent progress has demonstrated that defective carbons co-doped with heteroatoms ( e.g. N and S) usually have high activity. However, the role and contribution of the inherent defects and these dopants towards the ORR performance are still unambiguous. Herein, we have stepwise manipulated the heteroatom (N and S) doping, conversion and removal on carbon defects, combined with electrocatalytic performance evaluation, and systematically investigated the synergistic effect between the heteroatoms and carbon defects. The experimental results demonstrated that pyridinic- and pyrrolic-N atoms are more important than graphitic-N atoms for obtaining high ORR activity of the ORR catalyst and they could be considered as active N doping atoms. The synergistic effect of the active N doping atoms and defects is crucial for high ORR activity of the carbon catalyst. Without the active N species, only S doping provides a limited contribution for improving the catalysis performance of defective carbon. However, the S and active N co-doping on defective carbon could boost the acidic ORR performance of the catalyst with a high half-wave potential of 0.77 V in 0.1 M HClO 4 , which is superior to that of most metal-free electrocatalysts reported to date. This work provides an example of studying the catalytic contribution of multiple active centres from the perspective of synthesis control. The multiple active sites N, defect and S active sites were introduced gradually for obtaining an efficient carbon catalyst in acidic media.